2013
DOI: 10.1289/ehp.1206113
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Metabolic Syndrome, and Obesity in Relation to Serum Dioxin Concentrations: The Seveso Women’s Health Study

Abstract: Background: In animal studies, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) alters glucose transport and increases serum lipid levels and blood pressure. Epidemiologic evidence suggests an association between TCDD and metabolic disease.Objectives: On 10 July 1976, a chemical explosion in Seveso, Italy, resulted in the highest known residential exposure to TCDD. Using data from the Seveso Women’s Health Study (SWHS), a cohort study of the health of the women, we examined the relation of serum TCDD to diabetes, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 51 publications
4
72
0
Order By: Relevance
“…The NHANES 1999–2002 study showed an association between waist circumferences and BMI in subjects with detectable levels of POPs, making the chemicals plausible contributors to the obesity epidemic [92]. This also hold true for the adults, where a clear evidence for associations with the highly chlorinated PCBs and OC pesticide with existence or development of obesity [51, 79, 102, 103]. …”
Section: Endocrine Disrupting Chemicals (Pcbs Exposures) and Developmmentioning
confidence: 99%
“…The NHANES 1999–2002 study showed an association between waist circumferences and BMI in subjects with detectable levels of POPs, making the chemicals plausible contributors to the obesity epidemic [92]. This also hold true for the adults, where a clear evidence for associations with the highly chlorinated PCBs and OC pesticide with existence or development of obesity [51, 79, 102, 103]. …”
Section: Endocrine Disrupting Chemicals (Pcbs Exposures) and Developmmentioning
confidence: 99%
“…TCDD exposures are linked to several complex disease states in human cohorts including diabetes, metabolic syndrome, and cancer (Leng et al, 2014;Marinkovic et al, 2010;Uemura et al, 2009;Warner et al, 2013). TCDD is a potent activator of the aryl hydrocarbon receptor (AHR), an environment-sensing protein within the PAS superfamily (McIntosh et al, 2010).…”
mentioning
confidence: 99%
“…Acute TCDD exposure induces a wasting syndrome characterized by weight loss, adipose derangements, hyperlipidemia, ectopic lipid deposition, and hypoinsulinemia [79]. Conversely, multiple epidemiologic studies link TCDD to diabetes and hyper insulinemia [80,81]. In β-cell models, TCDD effects are similarly conflicting.…”
Section: Context-dependent MDC Actionmentioning
confidence: 99%